Ypt31/32 GTPases and Their Novel F-Box Effector Protein Rcy1 Regulate Protein Recycling - Chen, Shu Hui (The American Society for Cell Biology, 2005)
Ypt/Rab GTPases control various aspects of vesicle formation and targeting via their diverse effectors. We report a new role for these GTPases in protein recycling through a novel effector. The F-box protein Rcy1, which mediates plasma membrane recycling, is identified here as a downstream effector of the Ypt31/32 GTPase pair because it binds active GTP-bound Ypt31/32 and colocalizes with these GTPases on late Golgi and endosomes. Furthermore, Ypt31/32 regulates the polarized localization and half-life of Rcy1. This suggests that Ypt/Rabs can regulate the protein level of their effectors, in addition to the established ways by which they control their effectors. We show that like Rcy1, Ypt31/32 regulate the coupled phosphorylation and recycling of the plasma membrane v-SNARE Snc1. Moreover, Ypt31/32 and Rcy1 regulate the recycling of the furin-homolog Kex2 to the Golgi. Therefore, Ypt31/32 and Rcy1 mediate endosome-to-Golgi transport, because this is the only step shared by Snc1 and Kex2. Finally, we show that Rcy1 physically interacts with Snc1. Based on this result and because F-box proteins serve as adaptors between specific substrates and ubiquitin ligases, we propose that Ypt31/32 GTPases regulate the function of Rcy1 in the phosphorylation and/or ubiquitination of proteins that recycle through the Golgi.